Keloidal Scleroderma: Case Report and Review - Sama Kassira; Tarannum Jaleel; Peter Pavlidakey; Naveed Sami (Hindawi Limited, 2015)
Objective. We report a rare case of keloidal scleroderma and provide an analysis of similar cases. Results. A 41 year-old woman presented with dark brown, indurated, exophytic nodules over the chest along with smaller hyperpigmented plaques scattered over the abdomen, with concomitant sclerodactyly. The clinical, laboratory, and pathological findings were consistent with a diagnosis of keloidal scleroderma. The patient was treated with methotrexate, resulting in reduced firmness of her plaques and no new lesions. A literature review of previously reported cases was performed using keywords including keloidal morphea, keloidal scleroderma, nodular morphea, and nodular scleroderma. In our review, the majority of patients were African American and female. 91% of cases had nodular lesions with distribution on the trunk. The majority of patients exhibited sclerodactyly and pulmonary involvement was reported in 28%1. The majority of patients were ANA positive (63%) and only 10% demonstrated anti-SCL-70 positivity. Conclusion. Keloidal scleroderma is a rare presentation, which can often be clinically confused with keloid and scar formation. Due to this being a rare variant, our knowledge of treatment options and efficacy is limited. Methotrexate could be considered as an initial treatment option for patients with progressive keloidal scleroderma.